2016
DOI: 10.1016/j.celrep.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity between Epithelial and Mesenchymal States Unlinks EMT from Metastasis-Enhancing Stem Cell Capacity

Abstract: SummaryForced overexpression and/or downregulation of proteins regulating epithelial-to-mesenchymal transition (EMT) has been reported to alter metastasis by changing migration and stem cell capacity of tumor cells. However, these manipulations artificially keep cells in fixed states, while in vivo cells may adapt transient and reversible states. Here, we have tested the existence and role of epithelial-mesenchymal plasticity in metastasis of mammary tumors without artificially modifying EMT regulators. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
274
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(299 citation statements)
references
References 36 publications
(40 reference statements)
14
274
0
1
Order By: Relevance
“…Quantification of this niche-dependent advantage of an individual epithelial/mesenchymal phenotype was performed in an orthotopic MMTV-PyMT-driven mouse model of BC, which showed that the ratio of epithelial to mesenchymal cancer cells is 100: 1 in primary tumor, 15: 1 in blood and 150: 1 in lung metastases, presenting an advantage of the mesenchymal phenotype in circulation [22] . In another study of the MMTV-PyMTdriven BC mouse model [69] , the disproportion between epithelial and mesenchymal CTCs was not so significant, however much more widespread. Epithelial CTCs constituted from 0 to 80% (average 40%) of CTCs detected.…”
Section: Emt In Disseminationmentioning
confidence: 94%
See 1 more Smart Citation
“…Quantification of this niche-dependent advantage of an individual epithelial/mesenchymal phenotype was performed in an orthotopic MMTV-PyMT-driven mouse model of BC, which showed that the ratio of epithelial to mesenchymal cancer cells is 100: 1 in primary tumor, 15: 1 in blood and 150: 1 in lung metastases, presenting an advantage of the mesenchymal phenotype in circulation [22] . In another study of the MMTV-PyMTdriven BC mouse model [69] , the disproportion between epithelial and mesenchymal CTCs was not so significant, however much more widespread. Epithelial CTCs constituted from 0 to 80% (average 40%) of CTCs detected.…”
Section: Emt In Disseminationmentioning
confidence: 94%
“…It is possible that during their short transition in circulation (estimated CTC half-life 1-2.5 h [68] ), CTCs maintain the phenotype with which they entered the blood stream, and only at the distant site can changes in EMT status be observed. Beerling et al [69] showed that the percentage of E-cadherin low tumor cells is the same (60%) in circulation and in single cells which disseminated to the lungs (60%), but drops to 20% at the stage of 2-cell clusters and further to 0% at the stage of 3-cell clusters in the lungs. This progressive decrease in mesenchymal features at a distant site could represent the time frame required for mesenchymal cancer cells to revert back to the epithelial state in the absence of strong EMT cues present in the primary tumor or in the circulation.…”
Section: Staying Mesenchymal -Cooperation With Other Cellsmentioning
confidence: 99%
“…This indicates that cancer cells can rapidly switch between epithelial and mesenchymal states in vivo, which may support them in adapting to new environments and promoting secondary growth ( Fig. 2Bi; Beerling et al, 2016). Therefore, IVM can help to determine the epithelial-mesenchymal status of cancer cells and the optimal timing of drug treatment to most effectively counteract EMT and MET switching during the transit of cancer cells to secondary sites.…”
Section: Box 1 Subcellular Imaging Techniquesmentioning
confidence: 99%
“…De-regulated expression of the cell-cell junction protein Ecadherin is also often associated with EMT and cell invasiveness (Gregory et al, 2008;Lehmann et al, 2016b). Using a GEMM with fluorescent protein expression from the endogenous E-cadherin locus to monitor changes in E-cadherin expression intravitally, Beerling et al (2016) demonstrated epithelial-mesenchymal plasticity in breast cancer. They show that mesenchymal cells with low E-cadherin expression have a similar potential as epithelial cells with high E-cadherin expression to give rise to epithelial metastases.…”
Section: Box 1 Subcellular Imaging Techniquesmentioning
confidence: 99%
See 1 more Smart Citation